What is the age of flowering plants?. (19th April 2022) - Sauquet, Hervé; Ramírez-Barahona, Santiago; Magallón, Susana
Abstract : The age of flowering plants continues to be under intense scrutiny, yet remains largely unknown (from 140 to 270 million years) and determined by prior assumptions. Abstract: The origin of flowering plants (angiosperms) was one of the most transformative events in the history of our planet. Despite considerable interest from multiple research fields, numerous questions remain, including the age of the group as a whole. Recent studies have reported a perplexing range of estimates for the crown-group age of angiosperms, from ~140 million years (Ma; Early Cretaceous) to 270 Ma (Permian). Both ends of the spectrum are now supported by both macroevolutionary analyses of the fossil record and fossil-calibrated molecular dating analyses. Here, we first clarify and distinguish among the three ages of angiosperms: the age of their divergence with acrogymnosperms (stem age); the age(s) of emergence of their unique, distinctive features including flowers (morphological age); and the age of the most recent common ancestor of all their living species (crown age). We then demonstrate, based on recent studies, that fossil-calibrated molecular dating estimates of the crown-group age of angiosperms have little to do with either the amount of molecular data or the number of internal fossil calibrations included. Instead, we argue that this age is almost entirely conditioned by its own prior distribution (typically a calibration density set by the user in Bayesian analyses). Lastly, we discuss which future discoveries or novel types of analyses are most likely to bring more definitive answers. In the meantime, we propose that the age of angiosperms is best described as largely unknown (140–270 Ma) and that contrasting age estimates in the literature mostly reflect conflicting prior distributions. We also suggest that future work that depends on the time scale of flowering plant diversification be designed to integrate over this vexing uncertainty.